Monomorphic type of maculopapular cutaneous mastocytosis: rationale for interdisciplinary collaboration - E. I. Kasikhina; N. N. Potekaev; O. V. Zhukova; M. N. Ostretsova (Онкогематология)
Backround. Mastocytosis is a rare disease characterized by pathological accumulation of mast cells in one or more organs. According to the world Health Organization classification (2016), a monomorphic type of maculopapular cutaneous mastocytosis (monoMPCM) was identified among cutaneous clinical forms. In adolescents with monoMPCM (the “adult” type pattern), clinical manifestations persist into adulthood and can transform into a systemic process, so interdisciplinary monitoring of these patients is necessary.Aim. To analyze the clinical and laboratory features of the monomorphic type of MPCM in children and adolescents.Materials and methods. The study included data from 66 patients with monoMPCM who were undergoing outpatient treatment and observation at the Moscow Scientific and Practical Center of Dermatovenereology and Cosmetology. All patients underwent clinical, laboratory (basal serum tryptase), molecular (c-KIT gene mutation in exons 8–11, 17 by polymerase chain reaction), instrumental (ultrasound) examination of the abdominal organs and mesenteric lymph nodes. The serum interleukin 6 concentration was determined by flow cytometry using the ProcartaPlex™ Human Panel 1A Cytokine & Chemokine 34 plex multiplex analysis kit (eBioscience, Austria).Results. The median age of disease onset was 4 [3; 7] years (minimum age – 2 years, maximum – 16 years). The median value of basal serum tryptase was 10.9 (2.84–46.3) μg/L, among adolescents – 14 [10.8; 23.7] μg/L. Hepatosplenomegaly and enlarged mesenteric lymph nodes (mesadenitis) were diagnosed in 14 (21.2 %) patients with monoMPCM. The serum interleukin 6 concentration in patients with organomegaly was 10.1 [9.28; 25.5] pg/mL, which exceeded the reference values by 2.4 times. The KIT d816v mutation was detected in 3 (11.5 %) patients out of 26 examined patients with monoMPCM.Conclusion. The modern course of cutaneous mastocytosis demonstrates a tendency towards an increase in the number of cases and a more severe disease course in children. Particular attention should be paid to adolescents with monoMPCM and organomegaly, high serum tryptase levels and identified KIT d816v mutations in the peripheral blood as a risk group for the development of a systemic process.